FOUR CASES, THE SAME STORY? THE ROLES OF THE PRIME MINISTERS IN THE V4 COUNTRIES DURING THE COVID-19 CRISIS - Grendzinska, Joanna; Hoffman, Istvan; Klimovský, Daniel; Maly, Ivan; Nemec, Juraj (Babes-Bolyai University, 2022)
The goal of this paper is to deliver a comparative analysis of the behaviors and statements of the PMs in Hungary, Poland, Slovakia, and the Czech Republic, using the concept of adaptive leaderships as a base for analysis. We employed the usage of four fundamental skills proposed by Glover, Friedman and Jones (2002) and of five fundamental recommendations proposed by Macpherson and 't Hart (2020) to assess the behaviors and relevant statements of the PMs of the four analyzed countries during the time of the pandemic. The fact that all four analyzed PMs did not employ many adaptive leadership skills and recommendations may serve as one of the possible explanations for the very problematic results in fighting COVID-19 during the second phase of the pandemic, when especially the Czech Republic and Slovakia belonged to the most affected countries. The costs of such limited competence are borne by citizens and businesses.
ČTYŘI PŘÍPADY, STEJNÝ PŘÍBĚH? ROLE PREMIÉRŮ V ZEMÍCH V4 BĚHEM KRIZE COVID-19
Keywords: adaptive leadership; COVID-19 pan-demic; prime minister; central and eastern Europe; adaptivní vedení; pandemie covid19; premiér; střední a východní Evropa